With Job Satisfaction or Not? The Role of Job Satisfaction in the Relationship Between Training and Rewards on Employee Productivity - Ariani Misna; Tamara Dwinda; Malik Adera Rosviliana; Darma Dio Caisar (ECONOMICS)
With a harmonious pattern between the workforce and the company, job satisfaction will result. East Kalimantan is very popular for its abundant natural resources, including mining. Referring to the terminology above, this paper focuses on the causality between training and rewards on employee productivity by involving job satisfaction as a mediator. The focus of this paper is one of the largest companies operating in the mining sector located in the Balikapan area. The assessment was carried out by distributing an open questionnaire to 346 employees who worked at the company. The quantitative approach is implemented in Smart-PLS, where the output is two schemes (outer model and inner model). In general, the statistic analysis finds that training and rewards have direct implications for employee job satisfaction and productivity. At the same time, job satisfaction does not have direct implications for employee productivity. Unfortunately, job satisfaction is unable to mediate the relationship between training and rewards on employee productivity. In essence, although training and rewards function in stimulating job satisfaction and employee productivity, they have not been proven optimal in encouraging employee productivity which is mediated by job satisfaction. Therefore, companies need to prioritize job satisfaction with more comprehensive proportions.